The relationship between geometric design consistency and safety on rural single carriageways - O'MAHONY, MARGARET MARY (Association for European Transport, 2007)
Rural single carriageways in Ireland tend to fall below current design standards and have higher accidents rates (per vehicle kilometre) than roads designed to modern standards. Resources are not available to improve all rural single carriageways; therfore sections need to be identified as priority sections for improvement. Geometric design consistency studies can be used to identify inconsistent sections on highways, which can then be targeted for improvement. No geometric data exists for rural single carriageways in Ireland. A method of estimating geometric data from digital maps was implemented on some 70km of highways. 19 curves and 19 tangents were then selected to represent the overall geometric makeup of the highway. Numerous geometric indices were measured on site. A spot speed survey was conducted at the midpoint of each tangent and curve and operating speed was calculated for each site. The spot speed survey is used to estimate the operating speed on straights (tangents). An operating speed model is used to estimate the operating speed on curves. Using these estimated operating speeds a sample geometric design consistency evaluation is carried out. Elements were classified as good, fair or poor using a design evaluation criterion. An accident database for the N52 was obtained. Accidents that occurred on the N52 and were possibly caused by the road alignment were extracted from the database. 53 accidents at 40 locations were observed. 19 of these accidents occurred in locations that were classified good, 8 accidents occurred in locations classified fair and 13 accidents occurred in locations classified as poor. A relationship exists between geometric design consistency and safety. Of the 40 locations which had accidents over the 8 year period from 1999 ? 2005, 13 of these locations were detected as needing realignment by the geometric design consistency evaluation. A geometric design evaluation can be used to pin point locations on highways where accidents could conceivable be higher. Improvement works and resources can therefore be concentrated on these sections and hence rural single carriageways can be made safer.
European Transport Conference: 2007: Leeuwenhorst, The Netherlands
PUBLISHED
Keywords: road transport - Ireland; roads - Ireland